Como o aumento de temperatura devido às mudanças climáticas pode comprometer o serviço de polinização da abelha Mamangava Xylocopa frontalis na cultura do maracujá (Passiflora spp.) - Paiva, Letícia Ferreira (2023)
Bees are the most important pollinators for the majority ofangiosperms, including agricultural species. However, the increase inaverage global temperatures couldcompromise the survival and efficiency of many bee species as pollinators of wild and cultivated plants. Therefore, the present study aimed to investigate how temperature increase due to climate change can affectthe pollination service of the carpenter bee Xylocopa frontalisin passion fruit (Passifloraspp.) crops. The research was conducted at São José site,in Maranguape, Ceará,Brazil,in two adjacent areas of 0.5 ha, each planted with aspecies ofpassion fruit (P. edulis andP. cincinnata), and consisted of three experiments: (i) the effect of body temperature on the bee foraging behavior on passion fruit flowersunder different ambient temperature conditions;(ii) the pollination efficiency of X. frontaliswhile foraging passion fruit flowers under high ambient temperature conditions;and (iii) determination of critical and lethal temperatures ofX.frontalis. The results showed that the bees avoided foraging on passion fruit flowers as the temperature of the environmentandoftheir own bodiesincreased throughout the day, significantly (p<0.05) reducing the number and duration of flower visits inthe hottest hours of the day, from the rainy season (mildtemperatures) to the dry season (high temperatures). As a result, there was a deficit in natural pollination,and the values offruit set, fruit weight, pulp weight and seed numberwere below the potentialresultsduring the hottest time of the year. Finally, the critical (42.2 ± 1.31°C) and lethal (47.3 ± 1.79°C) temperatures ofX. frontaliswere determined. Thus, the study demonstrated that the increase in average ambient temperature, especially during the hours of the day andperiods of the year in whichit approached or exceeded the critical temperature ofX. frontalis, affected the bee's foraging behavioron passion fruit flowers, reducing its efficiency as a pollinator of the crop. This was particularly noticeable in P. edulis, whose flowers open at midday and have only a few hours in the afternoon for pollination. It wasconcluded that the pollination service of X. frontalisin P. edulis and P. cincinnatais already compromised during periods of higher temperatures, and further increases in average ambient temperature due to climate change could render the pollination of passion fruit by its natural pollinator unfeasible.